Deskripsi Tingkat Perundungan pada Siswa dengan Etnis Pendatang: Analisis perspektif Budaya - Reza Tririzky; Firman Firman; Yarmis Syukur (Badan Penerbit STIEPARI Press, 2025)
Bullying cases in the educational environment are a serious problem and demand attention from various parties. Bullying that occurs in the educational environment can be caused by a variety of conditions including differences in cultural values brought by students with immigrant ethnicities. Students with immigrant ethnicity will be a minority group that is vulnerable to bullying. This study aims to explore and describe bullying experienced by students with immigrant ethnicity in the school environment. A total of 47 students who were identified as having a background as ethnic migrants became respondents in this study. The results showed that 8.5% had high bullying experiences. This relatively low number is certainly inseparable from the role of native culture, namely Minangkabau culture, which upholds good values in interacting with others.